Purification of sorbitol using reverse osmosis membrane : effect of cross flow velocity and transmembrane pressure - Nur Athirah, Sabarudin (2014)
Sorbitol, a sugar alcohol that has formula of C6H14O6 also known as D-Glucitol. It can be obtained from the reduction of glucose, by changing the aldehyde group to hydroxyl group. It is very slow to metabolize in body, which lessen the chance of increasing the level of insulin, thus makes sorbitol is a good sweetener for diabetics. Since the use of sorbitol in the food industry more widely, sorbitol purity is a key factor before it is used as an additive in food. One of the method to purify sorbitol is application of membrane technology. However the membrane application is limited due tochallenges such as decay in permeate flux and increases the complexity of membrane operations. Thus, this research was conducted to study the effect of cross flow velocity (CFV) and transmembrane pressure (TMP) on the flux in purification of sorbitol using the reverse osmosis membrane. The flux was determined from the calculated of permeate flow rate divide by the area of spiral wound membrane. In order to study the optimize condition for the process, the value of TMP and CFV was varied to obtained the flux value. While varying the CFV value, the TMP value was constant and when the TMP was varied, the CFV was constant. This study was conducted for 60 minutes, and every 10 minutes the permeate flow rate was collected to get the flux value. The solution was prepared with constant concentration of 10g/L in a 100 L solution in tank. The determination of sorbitol was analyze by refractometer. Based on the result obtained, increasing in CFV and TMP give the highest flux value